2002
DOI: 10.1152/ajpregu.00117.2002
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory cycle timing and fast inspiratory discharge rhythms in the adult decerebrate rat

Abstract: Marchenko, Vitaliy, Antonio R. Granata, and Morton I. Cohen. Respiratory cycle timing and fast inspiratory discharge rhythms in the adult decerebrate rat. Am J Physiol Regul Integr Comp Physiol 283: R931-R940, 2002. First published June 27, 2002 10.1152/ajpregu.00117.2002In supracollicular decerebrate paralyzed adult rats, neural respiration was monitored by bilateral phrenic recordings. In the study of respiratory cycle timing, the effects of vagal afferent input (lung inflation) on respiratory phase durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 38 publications
(72 reference statements)
3
40
0
Order By: Relevance
“…These investigations have revealed fast oscillations in inspiratory nerve activities in both anesthetized and decerebrate rats in vivo, with the power spectrum most often characterized by a single spectral peak in either the MFO or HFO range (dual spectral peaks were rarely encountered). Furthermore, the peak frequencies associated with HFO activity were reported to be slightly higher in adult rats than those previously observed in other mammals; based on these recent observa-tions, the upper limit of the original HFO range has been extended to ϳ160 Hz (Kocsis and Gyimesi-Pelczer 1997;Marchenko et al 2002). Because the mouse is rapidly becoming a valuable model for studying the contribution of genetic factors in respiratory control (see recent review by Tankersley 2003), and to our knowledge, spectral composition of inspiratory-related activity in adult mouse has not yet been evaluated, we conducted this study, in part, to investigate the presence and location of fast oscillatory rhythms in inspiratory motor discharges in adult mouse in vivo.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…These investigations have revealed fast oscillations in inspiratory nerve activities in both anesthetized and decerebrate rats in vivo, with the power spectrum most often characterized by a single spectral peak in either the MFO or HFO range (dual spectral peaks were rarely encountered). Furthermore, the peak frequencies associated with HFO activity were reported to be slightly higher in adult rats than those previously observed in other mammals; based on these recent observa-tions, the upper limit of the original HFO range has been extended to ϳ160 Hz (Kocsis and Gyimesi-Pelczer 1997;Marchenko et al 2002). Because the mouse is rapidly becoming a valuable model for studying the contribution of genetic factors in respiratory control (see recent review by Tankersley 2003), and to our knowledge, spectral composition of inspiratory-related activity in adult mouse has not yet been evaluated, we conducted this study, in part, to investigate the presence and location of fast oscillatory rhythms in inspiratory motor discharges in adult mouse in vivo.…”
Section: Introductionmentioning
confidence: 76%
“…Because it has been suggested that spectral content in inspiratory motor discharges may change over the course of the inspiratory burst (Bruce 1986(Bruce , 1988Christakos et al 1989Christakos et al , 1991Cohen et al 1987b;Marchenko et al 2002;Richardson 1988;Richardson and Mitchell 1982;Schmid et al 1990;Webber 1989), time-frequency analyses using a generalized TFR with the SPWD kernel were performed on recordings of diaphragm EMG activity, phrenic nerve discharge, and hypoglossal nerve discharge to evaluate the time-varying (i.e., dynamic) features of spectral activity (see Time-frequency spectral analysis: SPWD). There existed, however, two possible outcomes regarding the TFR of the inspiratory motor discharges: 1) the inspiratory motor discharges would exhibit fast oscillatory components that are continuous during the inspiratory burst (i.e., time-invariant) or 2) the inspiratory motor discharges would exhibit fast oscillatory components that exist at particular times during the inspiratory burst (i.e., time-varying).…”
Section: Comparison Of Time-invariant and Time-varying Spectral Analysesmentioning
confidence: 99%
See 3 more Smart Citations